2017
DOI: 10.1186/s12974-017-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 in glial inflammatory responses to air pollution in vitro and in vivo

Abstract: BackgroundExposure to traffic-related air pollution (TRAP) is associated with accelerated cognitive aging and higher dementia risk in human populations. Rodent brains respond to TRAP with activation of astrocytes and microglia, increased inflammatory cytokines, and neurite atrophy. A role for Toll-like receptor 4 (TLR4) was suggested in mouse TLR4-knockouts, which had attenuated lung macrophage responses to air pollution.MethodsTo further analyze these mechanisms, we examined mixed glial cultures (astrocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 66 publications
7
90
0
1
Order By: Relevance
“…Recently, studies evaluating the extensive toxicity mediated by air pollution, especially particulate matter (PM2.5), have shown that these particles via several different routes, including a direct way by inhalation or ingestion and indirect routes by systemic responses in the human body, reach the brain and then damage the parenchyma of the CNS through the blood–brain barrier (BBB) [ 29 , 30 ]. In the adult brain, PM2.5 passes through the BBB, inducing the inflammatory responses via (1) glial activation [ 31 , 32 , 33 ], (2) amyloid toxicity [ 34 , 35 ], and (3) altered expression of the glutamatergic pathway genes [ 25 , 36 ]. Many studies on air pollution have focused on the effects of inhaled pollution in the respiratory systems, especially on the nose and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies evaluating the extensive toxicity mediated by air pollution, especially particulate matter (PM2.5), have shown that these particles via several different routes, including a direct way by inhalation or ingestion and indirect routes by systemic responses in the human body, reach the brain and then damage the parenchyma of the CNS through the blood–brain barrier (BBB) [ 29 , 30 ]. In the adult brain, PM2.5 passes through the BBB, inducing the inflammatory responses via (1) glial activation [ 31 , 32 , 33 ], (2) amyloid toxicity [ 34 , 35 ], and (3) altered expression of the glutamatergic pathway genes [ 25 , 36 ]. Many studies on air pollution have focused on the effects of inhaled pollution in the respiratory systems, especially on the nose and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Although autophagy may be involved in anti-inflammatory responses, autophagy may not play a significant role in LPS-induced inflammation since rafamycin treatment could improve pulmonary injury after LPS infection by down-regulating mTOR. As a result, there is a strong possibility of a signaling network between TLR4 and autophagy in the presence of PM-induced lung injury, with autophagy governed by a complex signaling network, and TLR4, a critical sensor of autophagy that is significantly involved in PM-induced immunity responses [36,37]. Since mTOR functions as a key autophagy checkpoint and is involved in PM-induced pulmonary inflammatory responses, it has been suggested that both the mTOR/autophagy and TLR4/MyD88 pathways affect lung injury [35].…”
Section: Discussionmentioning
confidence: 99%
“…Since mTOR functions as a key autophagy checkpoint and is involved in PM-induced pulmonary inflammatory responses, it has been suggested that both the mTOR/autophagy and TLR4/MyD88 pathways affect lung injury [35]. The TLR4-MyD88 pathway is considered an upstream signaling mediator of PM-induced pulmonary inflammatory responses, which induces the secretion or production of inflammatory cytokines and oxidants [36]. Oxidizing agents or other cytokines can inhibit mTOR activation, cause tissue cell autophagy, and lead to excessive inflammation and tissue damage [38].…”
Section: Discussionmentioning
confidence: 99%
“…This technology allows for a more comprehensive analysis than the filterable (i.e. water extracted) particulate samples examined in our prior studies (Morgan et al, 2011;Saffari et al, 2015;Verma et al, 2009;Woodward et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%